Diverse approaches to cloud brokering: innovations and issues. (2017) - Naha, Ranesh Kumar; Othman, Mohamed; Akhter, Nasrin
In the cloud computing concept, users can use computing resources according to their needs and requirements. The cloud approach helps users to reduce the cost of IT infrastructure. To provide services, different cloud service providers build their own computing platform differently due to the lack of a common standard. Selecting the cloud provider from among these heterogeneous cloud environments is really challenging for users. Several brokering mechanisms have been proposed as an intermediate solution in the past few years. Cloud brokering helps users to select a cloud provider according to their needs and specific requirements. In this paper, we present the ongoing research and innovations pertaining to the cloud brokering mechanism by various researchers. We also investigate various approaches, future challenges and other obstacles to all the proposed brokering solutions. The main contribution of this paper is that it provides the first review concerning cloud brokering architecture, which will provide a better understanding of cloud brokering and identify the important research directions of this increasingly important area. Another contribution is that it depicts a unified cloud brokering architecture that can contribute to future research.